A Feasibility Study of Women's Confidence and Comfort in Use of a Kit to Monitor Ovulation. (13th October 2015) - Ayoola, Adejoke B.; Slager, Dianne; Feenstra, Cheryl; Zandee, Gail L.
Abstract : Introduction: The focus of this study was to examine whether low‐income adult women will use ovulation test strips, a menstrual calendar chart, thermometer, temperature graph, and cervical mucus assessment to monitor their ovulation time and other menstrual changes. Women's confidence in their ability to detect ovulation time and understand the menstrual cycle changes were also examined. Methods: This is a descriptive study. Twenty‐two low‐income women aged 18 to 39 years living in medically underserved neighborhoods participated in this study. The women were introduced to and taught how to use a knowing your body (KB) kit, which consisted of ovulation test strips, monthly calendars for menstrual logs, digital thermometer for basal body temperature, and graphs to chart temperature. The women were interviewed 6 to 8 weeks later to confirm their experiences with the use of the KB kit. Results: Ninety‐one percent of the women used the ovulation test strips (mean, 3.8 strips); 77.3% were very to extremely confident that they could properly use the ovulation strip, 54.6% knew when they ovulated, and 31.8% could use the thermometer to confirm when they were ovulating. Seventy‐three percent of the women were very to extremely comfortable using the ovulation test strips, 81.8% using the thermometer, 45.5% using the temperature graph, and 31.8% using the TwoDay Method (cervical mucus observation). Discussion: The use of the ovulation test strip and other content of the KB kit provides a new opportunity for low‐income women to learn about their bodies by monitoring their ovulation time and other menstrual changes as a pregnancy planning and early pregnancy recognition tool.